The Effect of Using The Alternative Evaluation on Improving The Educational Outcomes of University Courses on Students (The Scientific Research Methodology Course as a Model) - Assaf, Mohammed; Naceur, Abdelmajid (FKIP-Universitas Riau, 2022)
This study sought to identify the effect of using alternative evaluation in improving educational outcomes. (Cognitive, psychological, skill) for university courses for students (the scientific research methodology course as a model). To achieve the objectives of the study, the researchers used the quasi-experimental method. The sample of the study consisted of (40) students enrolled in the course of scientific research methods at Al- Istiqlal University. They were distributed randomly into two groups: the experimental group used the alternative evaluation. However, the control group used traditional evaluation. The results of the study showed that there is an effect of using the alternative evaluation in improving the educational outcomes (cognitive, psychological, and skills) of the experimental group students. In light of these results, the researchers recommended a review of current evaluation practices that use traditional tests. In addition, there is a need to amend the regulations and instructions regulating the evaluation policy in accordance with the university's modernization and developing in line with modern strategies for evaluation, and the use of alternative evaluation tools in evaluating students' work in university courses.